Nutrition status, activity patterns and stress level of school age children during the covid-19 pandemic - Komang Yogi Triana; Made Pande Lilik Lestari; Ni Made Ari Sukmandari (Universitas Muhammadiyah Semarang, 2022)
The pandemic due to the Covid-19 virus has brought many changes to the world's social, economic, educational and healthy life. This condition has an impact on people's lives, not only adults but also children. Children have to adapt to various rules that change their daily habits. The purpose of this study was to identify a description of the nutritional status, activity patterns, and stress levels of school children in Bali Province during the Covid-19 pandemic. The research method used in this study is a quantitative method with a descriptive observational approach. Sampling was carried out using a simple random sampling technique involving 150 samples of children aged 9-13 years from 5 districts in Bali. The results showed that 68% of children were in good nutritional status and physical activity showed balanced results with the highest stress level of children being moderate stress which reached 88.7%. Parents and teachers have an important role in maintaining physical activity and children's mental health during the pandemic.